SOSIALISASI ANAK PADA KELUARGA TNI AD (STUDI KASUS TENTANG KELUARGA ANAK BERMASALAH DI LINGKUNGAN TNI AD) KELURAHAN TELUK BINJAI KOTA DUMAI - Syawaluddin "; Hesti Asriwandari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The study authors do in Kodim 0320 dorm in Teluk Binjai village, Dumaicity. This study entitled "Socialization of Children In Family Army (CaseStudy About Family of troubled children in Army Environment) TelukBinjai village, Dumai City". Topics focus of this research are the troubledchildren of the family of Army District Military Command 0320. In thisstudy, researchers used research informants through key informan whereresearcher have understood the initial information about the object ofresearch as well as research informants using simple random sampling.Informants in this study is a troubled child, a total of 5 children and 5families. The author uses qualitative descriptive method and the data wasanalyzed qualitatively. Data instrument is observation, interview anddocumentation. From research by the author, the authors conclude that thefamily is an important role in fostering and developing the character of achild in the family environment and outside environment. Family is veryimportant in child development. The survey results revealed thatrespondents (children) do mischief caused parents are busy with theiractivities due to the demands of the job, also because parents are too givesleeway against children, arises naughtiness that done by children outside thefamily environment.Keywords: family and troubled children